The acceptance of MTSB Skim Ansuran Murabahah MOCCIS (SAMM) among its customers at Campbell Complex, Kuala Lumpur / Nazimah Ibrahim - Ibrahim, Nazimah (2007)
The study was carried out at MOCCIS Trading Sdn. Bhd. Campbell Complex outlet, Kuala Lumpur Since MTSB has been operating its SAMM business for the past 10 years, this study is timely in gaining customers feedback towards their acceptance of SAMM. The findings in this study show that the reasons customers are attracted to consume SAMM can be attributed to its prices, the easy payment method, credit period given by MTSB, terms and conditions of agreement and application, customers confidence with the implementation of the Murabahah concept and also the range of products offered.